2018
DOI: 10.1002/chem.201802200
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembled, Fluorine‐Rich Porous Organic Polymers: A Class of Mechanically Stiff and Hydrophobic Materials

Abstract: Fluorous organic building blocks were utilized to develop two self-assembled, hydrophobic, fluorinated porous organic polymers (FPOPs), namely, FPOP-100 and FPOP-101. Comprehensive mechanical analyses of these functionalised triazine network polymers marked the introduction of mechanical stiffness among all porous organic network materials; the recorded stiffnesses are analogous to those of their organic-inorganic hybrid polymer congeners, that is, metal-organic frameworks. Furthermore, this study introduces a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…Recent investigations to measure the Young’s moduli of 2D COFs found values ranging from ∼10 MPa to 267 GPa, which spans over 4 orders of magnitude. It is still unclear whether such large variations can be entirely attributed to the different molecular structures of the COFs under study or are caused by the potential impact of factors such as the presence of structural defects and grain boundaries in the COF films. At this point of time, it remains a great challenge indeed to obtain few-layer, large-area 2D COFs, while routinely fabricated 2D COF films are often composed of aggregated small crystals, which complicate the characterization of their intrinsic mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Recent investigations to measure the Young’s moduli of 2D COFs found values ranging from ∼10 MPa to 267 GPa, which spans over 4 orders of magnitude. It is still unclear whether such large variations can be entirely attributed to the different molecular structures of the COFs under study or are caused by the potential impact of factors such as the presence of structural defects and grain boundaries in the COF films. At this point of time, it remains a great challenge indeed to obtain few-layer, large-area 2D COFs, while routinely fabricated 2D COF films are often composed of aggregated small crystals, which complicate the characterization of their intrinsic mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…44 Studies of mechanical stiffness of CTFs substituted with trifluoromethyl groups revealed behavior similar to glass polymers and zeolitic imidazolate frameworks. 45 Qi and coworkers have prepared fluorinated POPs (Figure 2, bottom right) by Pd-catalyzed C-H activation of 1,2,4,5-tetrafluorobenzene and its subsequent coupling with trigonal and tetrahedral aryl bromides. 46 Using ironporphyrin as a coupling partner, a series of fluorinated POPs was prepared with Brunauer-Emmett-Teller (BET) surface areas ranging between 670 and 840 m 2 g -1 .…”
Section: Covalent Organic Framework and Porous Organic Polymersmentioning
confidence: 99%
“…Several POPs with polar segments were prepared and tested in reversible water vapour capture from the air [ 19 , 20 ]. On the contrary, highly hydrophobic fluorine-rich POPs were also prepared [ 21 , 22 ] and applied to capture the vapour of non-polar hydrocarbons and fluorinated compounds. Application-interesting POPs with ionic [ 20 , 23 ], luminescent [ 24 ], chiral [ 25 , 26 ], and other groups [ 27 , 28 ] were also reported in the literature.…”
Section: Introductionmentioning
confidence: 99%